2022
DOI: 10.3389/fenvs.2021.838734
|View full text |Cite
|
Sign up to set email alerts
|

Does Carbon Emissions, and Economic Expansion Induce Health Expenditure in China: Evidence for Sustainability Perspective

Abstract: The current paper assesses the drivers of health care expenditure such as urbanization, natural resources, economic expansion, and CO2 utilizing quarterly data from 2000Q1 to 2018Q4. The research applied the novel dual adjustment approach to identify the long run association between healthcare expenditure and urbanization, economic growth, natural resource and CO2 emissions. The main novelty of the dual adjustment approach is that the approach offers another way to cointegration analysis by relaxing the implic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Air pollution caused by energy consumption in China increases public health costs, leading to higher social costs, increasing the burden of living and the Chinese government's fiscal spending. The same study in China also found the exact same result: economic growth, urbanisation and carbon dioxide (CO2) emissions increase health spending [4].…”
Section: Introductionmentioning
confidence: 63%
“…Air pollution caused by energy consumption in China increases public health costs, leading to higher social costs, increasing the burden of living and the Chinese government's fiscal spending. The same study in China also found the exact same result: economic growth, urbanisation and carbon dioxide (CO2) emissions increase health spending [4].…”
Section: Introductionmentioning
confidence: 63%
“…Furthermore, the two first studies identified a unidirectional causality, establishing a relationship among CO 2 emissions, economic growth, and both government and private health expenditures. Additionally, Xiu et al [53] affirmed a significant relationship and causality from the CO 2 emission to the health expenditures in the medium term. Li [52] focused on BRICS nations during the period 2000 -2019.…”
Section: Causality Link Between Variables and Co 2 Emissionsmentioning
confidence: 98%
“…Also, Aladejare (2022) showed that population growth substantially affected Nigeria's per capita public expenditure planning. Furthermore, Xiu et al (2022) submitted that urbanisation substantially increased public healthcare expenditure in China. Mirovic et al (2023) conducted a study for the Serbian economy using the ARDL model and found that population growth substantially affects government spending.…”
Section: Empirical Reviewmentioning
confidence: 99%